Fentanyl novel derivative‐related deaths. (21st June 2017) - Giorgetti, Arianna; Centola, Carmela; Giorgetti, Raffaele
Abstract: Objective: Fentanyl (FEN) is a potent, synthetic narcotic used as an anaesthetic and a pain reliever, but also illegally manufactured. For diversion purpose, it is being steadily modified to produce new analogous compounds and derivatives (FENS), categorised as novel psychoactive substances. While potential FEN abuse is already known, even in the absence of a clear lethal dosage, there is still a shortage of data on its derivatives. Methods: A literature review of FENS‐related deaths was performed, to better understand potential damage and future perspectives of FEN congeners. Results: Epidemiological data, pathological findings, administration routes, average concentrations and lethal doses, toxicological issues, trends in misuses, comparison among FENS, and possible explanation for FENS abuse are reviewed and discussed in depth. Conclusions: This study provides a medical–legal and toxicological assessment of this phenomenon in order to understand the role of illegal fentanyl and its congeners in deaths from FENS overdose.